Comparison of tunnel systems with geotextile strips and classical plug flow regime as an advanced wastewater treatment method - Avsar, Yasar; Tarabeah, Hussein; Kimchie, Shlomo; Naamneh, Hadi; Ozturk, Izzet (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2008)
This paper focuses on treatment performance characteristics of three reactors called tunnels 1, 2 and 3, with plug flow regime and different operating conditions, such as geotextile strips and aeration units. The effluent quality of wastewater increases towards the end of the tunnels. After a one-year monitoring programme, the tunnel 3, which included strips and aeration, was found to give the best results. At the end of tunnel 3, soluble chemical oxygen demand (sCOD), total suspended solids (TSS) and phosphate phosphorus (PO4-P) removal values were at the maximum level in 0.5 in depth, and that of ammonium nitrogen (NH4-N) in I in depth from the water surface, with the values 86.6%, 97.2%, 87.8% and 98.5%, respectively. Towards the middle and deeper zones of the tunnel, the effluent quality parameters deteriorate. Construction of tunnel 3 unit, with geotextile strips and aeration system, will be the best solution to revitalize/rehabilitate the seasonal reservoir (SR) unit of the wastewater treatment plant (WWTP).
Keywords: advanced treatment; sCOD; TSS; PO4-P; NH4-N; NITROGEN; Environmental Sciences & Ecology